Patterns of long-term survivorship following bevacizumab treatment for recurrent glioma: a case series - Liang Yen Liu; Matthew S Ji; Nhung T Nguyen; Frances E Chow; Donna M Molaie; Sean T Pianka; Richard M Green; Linda M Liau; Benjamin M Ellingson; Phioanh L Nghiemphu; Timothy F Cloughesy; Albert Lai (CNS Oncology, 2019)
Aim: Long-term survivors (LTS) after glioma recurrence while on bevacizumab (Bev) therapy are rarely reported in the current literature. The purpose of this case series is to confirm the existence of and describe a large cohort of recurrent glioma LTS treated with Bev (Bev-LTS). Patients & methods: We identified Bev-LTS as patients with post-Bev initiation survival times of ≥3 years among 1397 Bev treated recurrent glioma patients. Results: Among 962 grade-IV, 221 grade III, and 214 grade II Bev-treated glioma patients, we identified 28 (2.9%), 14 (6.3%) and 8 (3.7%) Bev-LTS patients, respectively. 45 Bev-LTS patients recurred on Bev, with 36 of those patients continuing therapy. Conclusion: Our study shows that a small portion of grade-IV, -III, and -II glioma patients can have long-term survival on Bev therapy even after Bev recurrence.